A cysteine protease of Paragonimus westermani eggs - Kang, S Y; Cho, M S; Chung, Y B; Kong, Y; Cho, S Y (Korean journal of parasitology, 1995)
Protease activity was identified in crude extracts of Paragonimus westermani eggs which were purified from infected dog lungs, isolated on 14 weeks after metacercarial challenge. The eggs were used after removing possibly contaminated host or worm tissues on their shell surfaces. In the crude egg extracts, high proteolytic activities against carboxybenzoyl-phenylalanyl-arginyl-4-methoxy-beta-naphthylamide (Cbz-phe-arg-MNA) and Azocoll were detected whereas those against succinyl-alanyl-prolyl- phenylalanyl-p-nitroanilide (Suc-ala-pro-phe-pNA) were not revealed. The enzyme exhibited the maximal activity at pH 6. Its activity was inhibited by specific cysteine protease inhibitors, 10(-5) M 1-trans-epoxysuccinylleucylamido (4-guanidino) butane (E-64) and 1 mM iodoacetamide (IAA) while potentiated by 6.5-fold in the presence of 2.5 mM dithiothreitol (DTT). When the enzyme was purified partially by Sephacryl S-300 High Resolution gel filtration, it migrated as a single homogeneous band at 35 kDa. The 35 kDa cysteine protease has been recognized neither in the metacercariae nor in the adult. These findings indicated the presence of at least one protease of cathepsin family in immature eggs of P. westermani.